Strategi Intervensi untuk Meningkatkan Attachment antara Orangtua dan Anak dengan Autism Spectrume Disorder: Tinjauan Literatur - Calvina Izumi; Amalia Rahmdhani; Vevriyani Effendi; Hanifa Laura Dalimunthe (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Children with Autism Spectrum Disorder (ASD) face unique challenges in building attachment relationships, due to ASD children experiencing impairments in communication, social interaction, and emotional regulation. This study aims to identify effective intervention strategies to improve the quality of attachment between parents and children with ASD through a Systematic Literature Review (SLR) approach. The review findings indicate that several interventions have proven effective in enhancing attachment between parents or primary caregivers and children with ASD, including the following interventions: DIR/Floortime, Focused Playtime Intervention (FPI), Parent-Child Interaction Therapy (PCIT), Circle of Security (COS), Positive Behavior Support (PBS), play training, massage therapy, and psychoeducation. The results of these interventions show that changes occur before and after the intervention, including strengthening two-way communication, increasing parental sensitivity, and improving the child's emotional responses. These findings have practical implications for parents, educators, and therapists in designing attachment-based approaches to support the social and emotional development of children with ASD. Responsive and supportive designing attachment-based approaches to support the social and emotional development of children with ASD. Responsive and supportive relationship-based interventions can build secure attachments between children with ASD and their parents and serve as an important reference in attachment-based parenting and therapy practices.